Rheological and textural properties of lafun, a stiff dough, from improved cassava varieties - Bouniol, Alexandre; Adinsi, Laurent; Padonou, Sègla Wilfrid; Hotegni, Francis; Gnanvossou, Désiré; Tran, Thierry; Dufour, Dominique; Joseph, Djidjoho; Akissoé, Hounhouigan Noël (Wiley, 2021)
We studied the textural and rheological (viscoelastic) properties of fresh lafun dough, a fermented cassava product, and their changes during storage at 45 °C for 5 and 24 h, in order to determine after‐cooking storability. Lafun flours were produced from three types of cassava varieties: seven improved white‐fleshed varieties, seven improved provitamin A carotenoids (pVAC) varieties and two local white‐fleshed varieties; and processed into lafun doughs. Pasting properties of the flours were assessed. Flours from local varieties had pasting profiles with highest viscosities, while pVAC flours had the lowest. The three types of cassava varieties varied significantly in most of their pasting properties. Four promising improved varieties were identified, based on high peak viscosity (55.8–61.5 P) and stiffer texture than local varieties during storage. Undesirable varieties were also found, which softened during storage instead of hardening. Optimum texture of lafun dough was obtained after 5 h of storage.